Smart Living Tourism: Safe and Comfort Natural Tourism Concept - Lustina Fajar Prastiwi; Sri Handayani; Sunil Kumar Chaudary (Universitas Ahmad Dahlan, Yogyakarta, 2023)
This research is a literacy study about smart living tourism in Indonesia. The aim is to find out the opportunities that smart living tourism has to develop through a review of existing literature. This study uses a descriptive and qualitative methodologies. Researchers try to uncover and understand something behind phenomena that have not been known before so that they can provide complex details about phenomena that are difficult to uncover in previous research. The result is smart living tourism Indonesia has a wide opportunity as a new nature tourism entity. With the existence the usage of websites, social media, and the internet can speed up marketing and increase consumer convenience in consuming this tourism commodity because it is easy and fast. What's more, smart living tourism is very close to nature, adding to the variety of ways tourists can enjoy nature. The contribution of this article is to provide knowledge that the trend of mart living tourism is becoming quite promising as a way to increase income in the tourism sector by collaborating between lodging tourism and nature tourism.